Variation in gravimetric correction factors for nephelometer-derived estimates of personal exposure to PM2.5. (July 2019) - Tryner, Jessica; Good, Nicholas; Wilson, Ander; Clark, Maggie L.; Peel, Jennifer L.; Volckens, John
Abstract: Many portable monitors for quantifying mass concentrations of particulate matter air pollution rely on aerosol light scattering as the measurement method; however, the relationship between scattered light (what is measured) and aerosol mass concentration (the metric of interest) is a complex function of the refractive index, size distribution, and shape of the particles. In this study, we compared 33-h personal PM2.5 concentrations measured simultaneously using nephelometry (personal DataRAM pDR-1200) and gravimetric filter sampling for working adults (44 participants, 249 samples). Nephelometer- and filter-derived 33-h average PM2.5 concentrations were correlated (Spearman's ρ = 0.77); however, the nephelometer-derived concentration was within 20% of the filter-derived concentration for only 13% of samples. The nephelometer/filter ratio, which is used to correct light-scattering measurements to a gravimetric sample, had a median value of 0.52 and varied by over a factor of three (10th percentile = 0.35, 90 th percentile = 1.1). When 33-h samples with >50% of 10-s average nephelometer readings below the nephelometer limit of detection were removed from the dataset during sensitivity analyses, the fraction of nephelometer-derived concentrations that were within 20% of the filter-derived concentration increased to 25%. We also evaluated how much the accuracy of nephelometer-derived concentrations improved after applying: (1) a median correction factor derived from a subset of 44 gravimetric samples, (2) participant-specific correction factors derived from one same from each subject, and (3) correction factors predicted using linear models based on other variables recorded during the study. Each approach independently increased the fraction of nephelometer-derived concentrations that were within 20% of the filter-derived concentration to approximately 45%. These results illustrate the challenges with using light scattering (without correction to a concurrent gravimetric sample) to estimate personal exposure to PM2.5 mass among mobile adults exposed to low daily average concentrations (median = 8 μg m −3 in this study). Graphical abstract: Image 1 Highlights: Nephelometer- and filter-derived PM2.5 concentrations were correlated (ρ = 0.77). The nephelometer tended to underestimate the filter measurement by ∼50%. The nephelometer/filter ratio was sensitive to nephelometer readings below 3 μg m −3 Gravimetric correction factor varied by 300% between the 10th and 90 th percentiles. Modeled corrections brought 45% of nephelometer concentrations within 20% of filter. Abstract : Variations in the factor used to correct nephelometer data to a gravimetric sample present challenges for estimating personal exposure to PM2.5 mass.